2012
DOI: 10.1103/physreve.86.036316
|View full text |Cite
|
Sign up to set email alerts
|

Taylor dispersion with adsorption and desorption

Abstract: We use a stochastic approach to show how Taylor dispersion is affected by kinetic processes of adsorption and desorption onto surfaces. A general theory is developed, from which we derive explicitly the dispersion coefficients of canonical examples such as Poiseuille flows in planar and cylindrical geometries, in both constant and sinusoidal velocity fields. These results open the way for the measurement of adsorption and desorption rate constants using stationary flows and molecular sorting using the stochast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…The resulting Poiseuille flow induces Taylor-Aris dispersion [32,33] of the tracers with a dispersion coefficient K, which is known exactly in the presence of adsorption and desorption in the simple slit geometry [5]: (15) where P e = Lv/D b is the Péclet number and y = k a /k d L.…”
Section: -3mentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting Poiseuille flow induces Taylor-Aris dispersion [32,33] of the tracers with a dispersion coefficient K, which is known exactly in the presence of adsorption and desorption in the simple slit geometry [5]: (15) where P e = Lv/D b is the Péclet number and y = k a /k d L.…”
Section: -3mentioning
confidence: 99%
“…Recently, the great interest in nanofluidic devices and in the transport in heterogeneous porous media has also raised the issue of the relevance of models which do not take into account these sorption processes. Moreover, it was recently shown that stochastic resonance between these processes and some external field may be of practical importance, e.g., for molecular sorting [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their high modularity, combination of large surface area and pore volume, and enhanced permeability over materials with single pore systems, hierarchically structured porous materials are promising candidates as adsorbent for the separation of gas and liquids, as well as for ion exchange and capture. [13][14][15] We first describe the simulation algorithm used to compute our simulations: a lattice Boltzmann scheme which allows to account for adsorption. heavy metals or radioactive ions.…”
Section: Introductionmentioning
confidence: 99%
“…When the particle has zero velocity and diffusivity in the bound state, D is given by 5,16,20,23,28,34 …”
Section: Introductionmentioning
confidence: 99%